Eksperimen Pembelajaran Matematika Dengan Strategi Problem Based Learning Dan Project Based Learning Terhadap Hasil Belajar Ditinjau Dari Kerja Keras Siswa Kelas VII SMP Negeri 4 Klaten Semester Gasal Tahun Ajaran 2015/2016 - Wati, Dian Ratna (2016)
There are three aims of the research. (1) Examine the effects of Problem Based Learning and Project Based Learning strategy toward mathematics learning achievement. (2) Examine the effects of hard work toward mathematics learning achievement. (3) Examine the interaction between learning strategy and hard work toward mathematics learning achievement. The type of the research was a quantitative research with quasi experimental design. The population of the research was all students of VII Grade of SMP Negeri 4 Klaten of odd semester of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use simple random sampling. Methods of data collection use the test, questionnaires, and documentation. Data were analyzed use analysis of variance with two different cell lines. The findings of the research with a=5%. (1) There was a effects of Problem Based Learning and Project Based Learning strategy toward mathematics learning achievement, (2) there was a effects of hard work toward mathematics learning achievement, (3) There was no interaction between learning strategy and hard work toward mathematics learning achievement.